Study on russet-related enzymatic activity and gene expression in 'Shine Muscat' grape treated with GA3 and CPPU. Issue 1 (1st January 2018) - Hou, Xudong; Wei, Lingling; Xu, Yanshuai; Khalil-Ur-Rehman, Muhammad; Feng, Jiao; Zeng, Jinjue; Tao, Jianmin
ABSTRACT: Physiological (metabolite analysis) and molecular (gene expression) approaches were used to understand the mechanism underlying russet formation in response to the application of GA3 and CPPU (Forchlorfenuron) in a Japanese table grape cultivar 'Shine Muscat'. Several different concentrations of GA3 and GA3  + CPPU [25 mg L −1 GA3 (A), 25 mg L −1 GA3  + 5 mg L −1 CPPU (B), 25 mg L −1 GA3  + 10 mg L −1 CPPU (C), and 25 mg L −1 GA3  + 15 mg L −1 CPPU (D)] were applied to grape berry clusters at two weeks after flowering (WAF). No russet was observed on the berries treated with the 'C' combination. Lower levels of phenylalanine ammonia-lyase (PAL) activity was observed in the treated samples, relative to the untreated material. Reduced peroxide (POD) activity was also observed in response to different treatments, while the expression of Peroxidase 17 and Phenylalanine ammonia-lyase G1 genes mirrored lignin content. Increased activity of 4-coenzyme A ligase (4CL) may contribute to decreasing the level of russet and help to improve grape berry quality.